Iron oxide magnetic nanoparticles supported on amino propyl‐functionalized KCC‐1 as robust recyclable catalyst for one pot and green synthesis of tetrahydrodipyrazolopyridines and cytotoxicity evaluation. (9th January 2020) - Azizi, Sajjad; Soleymani, Jafar; Hasanzadeh, Mohammad
Abstract : In this study, paramagnetic dendritic fibrous nano‐silica functionalized by aminopropyltriethoxysilan (Fe3 O4 @KCC‐1‐nPr‐NH2 ) was synthesized using a novel hydrothermal protocol and used as a highly efficient, recyclable and heterogeneous nanocatalyst for the synthesis of a wide range of tetrahydrodipyrazolopyridines derivatives (5a‐5 m ). The influence of different reaction parameters, such as the effects of solvent, temperature, time and concentration of catalyst for the synthesis of tetrahydrodipyrazolopyridine (2a) were studied. This catalyst could be reused for ten consecutive recycles without any considerable loss in its catalytic activity. This novel synthesis method offers some advantages including short reaction time, high yield and simple work‐up procedure. Finally, the newly synthesized tetrahydrodipyrazolopyridines derivatives (5a‐5f ) were characterized by 1 H and 13 C NMR, IR and CHN. Abstract : Fe3O4@KCC‐1‐nPr‐NH2 was synthesized using a novel hydrothermal protocol and used as a highlyefficient, recyclable and heterogeneous nanocatalyst for the synthesis of awide range of tetrahydrodipyrazolopyridines derivatives